Wujud Akulturasi Hindu, Budha, dan Islam dalam Seni Pertunjukan Wayang - Fitri Nuraisyah; Hudaidah H (UIN Sunan Gunung Djati Bandung, 2021)
This article deals with the form of acculturation of Hinduism, Buddhism, and Islam in wayang performing arts”, the writing of this article aims to analyze the results of Hindu-Buddhist acculturation on wayang performance art and the results of Islamic acculturation in the art of wayang performance. The method used in writing this article is literary study which is used as a data source. The results of writing this article are in the form of acculturation, which means that it is a combination of two different cultures that do not eliminate elements from the old culture. In this article, we discuss acculturation in the art of wayang performance. Wayang is a puppet played by a puppeteer. Wayang has undergone acculturation based on its era, where at the beginning wayang was considered as a shadow of ancestral spirits so that the puppet show ceremony is often performed by the ancestors. Then after Hindu-Buddhist religion came, wayang was used as a medium to spread the Buddhist religion by including stories from the Mahabharata and the Ramayana. After the waning of Hindu-Buddhist influence, the nine wali also carried out the spread of religion and teachings of Islam. The guardians acculturate the values of Islamic teachings with wayang. During the Islamic period, there was a change in the form of wayang from before because the previous form of wayang was contrary to Islamic teachings so that the puppet was changed into a form that did not resemble humans. Keywords: acculturation, Hindu Buddhist Islam, Wayang